Second Language Acquisition Three Year Old Children in the Angkola Batak Tribe - Jusrin Efendi Pohan Jusrin Efendi Pohan (Faculty of Letters Universitas Balikpapan, 2023)
This study provided about the acquiring language in three years old boy in small family scope. The main point of this research was Batak Angkola boy who spoke Indonesian in Padangsidimpuan. The data which were used for this analyzing was authentic had got by making observation. These data were also analyzed based on three main features is analyzing based on the sentence structure; analyzing based on sentence pattern, and analyzing based on the quantity of data utterances in each utterances. The acquisition language in three years old boy was founded that the sentences were not complete yet in his utterances and it was usually simple sentence. Based on the number of utterances for each speech turn, it is proven that a three year old child in speaking only answers questions from the interlocutor. This study is still far from perfect. The scope of the discussion which was originally deliberately used to limit this study, is not impossible, but it is actually dwarfing the scope of the discussion.